Application of post-processing technique in diagnosis of coronary computed tomography angiography imaging. Issue 7 (April 2020) - Zhang, Tianqi; Xu, Nannan; Gong, Tingting; Li, Bo; Liu, Jianhua; Yuan, Qinghai; Wang, Lei
Abstract: Coronary artery disease (CAD) as a common chronic disease, acute myocardial infarction (AMI) is one of the most urgent manifestations of CAD which had a highly mortality. Coronary computed tomography angiography (CCTA) combined with post-processing technique was the best way to diagnosis CAD in routine examination. By various postprocessing techniques, such as Volume rendering (VR), Curved planar reformations (CPR) techniques can speed up the complicated processing of CCTA and improve the diagnostic accuracy of radiologists.